2003
DOI: 10.18388/abp.2003_3637
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an antioxidant: biochemical mechanisms and pathophysiological implications in humans.

Abstract: This brief resume enumerates the multiple actions of melatonin as an antioxidant. This indoleamine is produced in the vertebrate pineal gland, the retina and possibly some other organs. Additionally, however, it is found in invertebrates, bacteria, unicellular organisms as well as in plants, all of which do not have a pineal gland. Melatonin's functions as an antioxidant include: a), direct free radical scavenging, b), stimulation of antioxidative enzymes, c), increasing the efficiency of mitochondrial oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
289
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(304 citation statements)
references
References 108 publications
7
289
1
7
Order By: Relevance
“…This was likely due to the rise of the circulating serum levels of melatonin produced by the exogenous administration of its precursor, and indicates that rising serum levels of melatonin are accompanied by a decline in the levels produced by heterophils. This confirms previous studies that have shown melatonin to be a powerful direct free radical scavenger and general antioxidant, which reduces oxidative damage at both physiological and pharmacological concentrations [27]. In earlier studies, a decline in levels and in lipid peroxidation after incubation of heterophils from old animals with the physiological melatonin concentrations found in young animals had been observed [28,29]; furthermore, we observed…”
Section: Discussionsupporting
confidence: 92%
“…This was likely due to the rise of the circulating serum levels of melatonin produced by the exogenous administration of its precursor, and indicates that rising serum levels of melatonin are accompanied by a decline in the levels produced by heterophils. This confirms previous studies that have shown melatonin to be a powerful direct free radical scavenger and general antioxidant, which reduces oxidative damage at both physiological and pharmacological concentrations [27]. In earlier studies, a decline in levels and in lipid peroxidation after incubation of heterophils from old animals with the physiological melatonin concentrations found in young animals had been observed [28,29]; furthermore, we observed…”
Section: Discussionsupporting
confidence: 92%
“…Melatonin promotes the NADPH-dependent GSSG reduction by GRx [37], surpassing the needs for GSH [38], which is consistent with higher GRx activity in the presence of melaxen. The increase in GSH and aMT6s support these observations and indicate that melatonin activity can be connected with the expression of antioxidant enzymes [16]. The decrease in GST activity may be associated with competition of the GPx/GRx system for GSH.…”
Section: Discussionsupporting
confidence: 71%
“…A number of physiological and pharmacological effects of melatonin have been considered in relation to its antioxidant activity [31]. The antioxidant effects of melatonin is due to the various complex mechanisms including upregulation of antioxidant and downregulation of pro-oxidant enzymes, suppression of mitochondrial radical formation and free radical scavenging [32].…”
Section: Discussionmentioning
confidence: 99%